2010
DOI: 10.1177/0022034510388037
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Tumor Cell Radiation Response Occurs in the Presence of IGF1

Abstract: Radiation therapy for head and neck cancer results in severe secondary side-effects in salivary glands. We previously demonstrated that the administration of IGF1 preserves or restores salivary gland function following radiation. Based on these findings, we propose to study the effect of IGF1 on human head and neck carcinoma cells. Head and neck tumor cells treated with radiation have significant reductions in tumor cell survival, as measured by MTT and crystal violet assays, regardless of IGF1 pre-treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We would expect that high levels of serum IGF1 would be also associated with head and neck cancers, however, Brady et al showed that circulating levels of both IGF1 and IGFBP3 protein is decreased in head and neck cancer patients [27]. On the other hand there is an evidence that IGF1 therepy for head and neck cancer undergoing radiation therapy may help with preservation and restoration of silvary gland function after radiation therapeutical approach [28]. Yet, the study of oral cancer cell line showed that there is positive association between autocrine production of IGF2 together with overexpression of IGF1-R and enhanced proliferation of oral cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…We would expect that high levels of serum IGF1 would be also associated with head and neck cancers, however, Brady et al showed that circulating levels of both IGF1 and IGFBP3 protein is decreased in head and neck cancer patients [27]. On the other hand there is an evidence that IGF1 therepy for head and neck cancer undergoing radiation therapy may help with preservation and restoration of silvary gland function after radiation therapeutical approach [28]. Yet, the study of oral cancer cell line showed that there is positive association between autocrine production of IGF2 together with overexpression of IGF1-R and enhanced proliferation of oral cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…More recent data, however, suggest that SOCS proteins and especially SOCS2 may also modulate IGF1R-mediated signaling [13], [14]. Importantly, preclinical and translational studies show that components of the IGFR-mediated pathway are implicated in SCCHN risk [15], angiogenesis [16], pharmacogenetics [17], [18], chemosensitivity [19], immunotherapy [20] and radiation response [21].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, our study suggests that the endogenous pool of salivary LRCs may be stimulated with IGF-1 to promote regeneration. However, although post-therapeutic administration of IGF-1 did not affect tumor growth rates in a xenograft model 50 , systemic administration of growth factors, such as IGF-1, raises concern of increasing the risk of developing de novo malignancies 51 , 52 . One way to circumvent this shortcoming is to develop a delivery mechanism, such as nanoparticles, that allows for targeted administration to the salivary glands.…”
Section: Discussionmentioning
confidence: 99%